Considerations for Selection and Use of Ornamental Grasses - Mack Thetford (EDIS)
Ornamental grasses are one of the most interesting and exciting groups of plants to be introduced to the landscape market in the past few years. The availability of a large number of species and cultivars makes these plants very versatile with many potential uses in the landscape. The diversity of grasses has also led to many questions concerning the proper selection and use of ornamental grasses. The information in this document should assist the first time gardener as well as the experienced landscaper in the selection and use of ornamental grasses in Florida. This document is ENH976, one of a series of the Environmental Horticulture Department, UF/IFAS Extension. Original publication date March 2004. Revised January 2006.